Adsorption rectification filler based on hydrogel 3D printing and application of adsorption rectification filler in preparation of electronic-grade chemicals

By adsorption and distillation fillers prepared based on hydrogel 3D printing, combined with the coupling of adsorption and distillation processes, the problem of difficult to remove trace metal ions during distillation in the prior art is solved, and efficient metal ion removal and electronic-grade chemical preparation are achieved.

CN119838581AActive Publication Date: 2025-04-18FUZHOU UNIV +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510148295.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-18
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove trace metal ions from electronic grade chemicals during distillation, resulting in a sharp increase in the number of theoretical plates required for the distillation tower and high energy consumption.

Method used

Adsorption and distillation fillers based on hydrogel 3D printing are prepared by photoinitiators, light absorbers, solvents and crosslinkers that do not contain metal ions, and adsorption and distillation fillers are printed and prepared by using 3D printing photocuring technology. Combined with the coupling of adsorption and distillation processes, trace amounts of metal ions in chemicals are removed.

Benefits of technology

The number of columns of the distillation tower is effectively reduced, the cost of building an adsorption tower is avoided, and the metal ions in NMP, IPA, and PMA are removed to less than 1 ppb, realizing the preparation of electronic chemicals above G3 level.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838581A_ABST
    Figure CN119838581A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of an adsorption rectification filler based on hydrogel 3D printing and application of the adsorption rectification filler in preparation of electronic-grade chemicals. Different from a traditional preparation method of 3D printing hydrogel, hydrogel ink for 3D printing is prepared from a cross-linking agent without metal ions, a photoinitiator, a light absorbent and a solvent, an adsorption rectification filler is printed and prepared by adopting a 3D printing photocuring technology, and then the prepared adsorption rectification filler is filled in a rectifying tower, so that the 3D printing hydrogel is prepared. Through coupling of adsorption and rectification processes, trace metal ions in chemicals such as N-methyl pyrrolidone (NMP), propylene glycol monomethyl ether acetate (PMA) or isopropyl alcohol (IPA) and the like are effectively removed, so that the content of the metal ions in the chemicals reaches 1 ppb or below, and the preparation of electronic-grade chemicals of G3 or above is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of 3D printed hydrogel new materials and new applications, and specifically relates to an adsorption and distillation filler based on hydrogel 3D printing and its application in the preparation of electronic-grade chemicals. Background Art

[0002] Electronic chemicals, also known as electronic chemical materials, generally refer to special chemicals and chemical materials used in the electronics industry. Their products have strong professional requirements and high differentiation. Most of the electronic chemicals used in my country rely on imports, which seriously affects the development of high-end electronic fields such as chips, integrated circuits and 5G in my country. With the rapid development of integrated circuit technology, the purity requirements for electronic-grade chemicals are getting higher and higher. The requirements for particle impurity content have been reduced from 1 μm to 0.5 μm and even 0.2 μm, and the purity must reach at least 6N (99.9999%). Some even require a purity of 9N or more (99.9999999%), and the content of metal ion impurities has also developed from Grade 3 (≤1ppb) to Grade 4 (≤0.1 ppb). Therefore, the removal of metal ions in electronic chemicals is one of the key issues in the development of microelectronics technology. It is crucial to develop a functional material for the removal of metal ions in organic solvents such as NMP, IPA, and PMA.

[0003] Wet electronic chemicals such as N-methylpyrrolidone (NMP), isopropyl alcohol (IPA), and propylene glycol monomethyl ether acetate (PMA) are mainly used in high-end fields such as electrolytes for lithium-ion batteries, cleaning agents for liquid crystal products, and photoresist stripping solutions. At present, the purification and removal of organic solvents such as NMP, IPA, and PMA are mostly carried out by continuous distillation, which can remove trace metal ions while removing impurities such as organic matter and water. However, for electronic-grade chemicals, since the content of metal ions needs to be reduced from ppm to ppb, the number of theoretical plates required for the distillation process increases dramatically, and the energy consumption is high. Therefore, it is crucial to find a way to effectively remove metal ion impurities during the distillation process and prepare electronic-grade chemicals.

[0004] Adsorption is one of the most promising methods for deep removal of metal ion impurities because it can accurately design the adsorption material. Therefore, the preparation of an adsorption distillation filler is of great significance for the preparation of electronic-grade chemicals. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing an adsorption distillation filler based on hydrogel 3D printing and its application in preparing electronic-grade chemicals.

[0006] To achieve the above object, the present invention adopts the following technical solutions: One of the purposes of the present invention is to protect an adsorption distillation filler based on hydrogel 3D printing, which is prepared by using a photoinitiator, a light absorber, a solvent and a cross-linking agent that do not contain metal ions to prepare a 3D printing hydrogel ink, and then printing it using 3D printing photocuring technology.

[0007] The second object of the present invention is to protect the preparation method of the adsorption distillation filler, which comprises the following steps: (1) L-lysine, a reactive monomer, ammonium persulfate, a crosslinking agent, a photoinitiator, and a light absorber are mixed, and electronic grade ammonia, acrylic acid, and ultrapure water are added under stirring to prepare a 3D printing hydrogel ink; (2) According to the designed filler three-dimensional model, photocuring 3D printing is performed using the 3D printing hydrogel ink prepared in step (1) to obtain a photocured hydrogel adsorption distillation filler structure; (3) The hydrogel adsorption distillation filler structure obtained in step (2) is subjected to ion exchange with a hydrochloric acid solution, and freeze-dried to obtain the adsorption distillation filler.

[0008] Furthermore, the reaction monomer in step (1) is cellulose or sodium lignin sulfonate.

[0009] Furthermore, the cross-linking agent in step (1) is N,N-methylenebisacrylamide or polyethylene glycol diacrylate.

[0010] Furthermore, the photoinitiator in step (1) is (2,4,6-trimethylbenzoyl) diphenylphosphine oxide (TPO) or ethyl 2,4,6-trimethylbenzoyl phenylphosphonate (TPO-L).

[0011] Furthermore, the light absorber in step (1) is tartrazine, riboflavin or ultraviolet absorber UV-P.

[0012] Furthermore, the mass ratio of L-lysine, reactive monomer, ammonium persulfate, crosslinking agent, photoinitiator and light absorber used in step (1) is 1:(1-3):5:1:(0.4-1):(0.1-0.5).

[0013] Furthermore, in step (1), the amounts of electronic grade ammonia water, acrylic acid and ultrapure water used account for 21-30%, 38-49% and 20-30% of the mass of the obtained hydrogel ink for 3D printing, respectively.

[0014] Furthermore, the electronic grade ammonia water does not contain metal ions. The conductivity of the ultrapure water is 18.2 MΩ, and the TOC value is less than 5 ppb.

[0015] Furthermore, the three-dimensional model of the filler designed in step (2) includes filler results such as a foam structure, a corrugated structure, and a columnar structure.

[0016] Furthermore, the designed packing includes surfaces with openings, non-openings, openings with windows, threads, etc.

[0017] Furthermore, the light source wavelength used in the light-curing 3D printing in step (2) is 320-500 nm, the light source intensity is 300-500 mW, the exposure time of each layer is 10-30 s, and the slice thickness is 0.1-0.2 mm.

[0018] Furthermore, the concentration of the hydrochloric acid solution used in step (3) is 1-5 M.

[0019] Furthermore, the ion exchange time in step (3) is 2-12 hours.

[0020] Furthermore, the freeze-drying temperature in step (3) is -40~50°C.

[0021] The third purpose of the present invention is to protect the application of the adsorption distillation filler in removing trace metal ions in chemicals by adsorption distillation and preparing electronic grade chemicals.

[0022] Specifically, the application method is to load the adsorption distillation filler into a distillation tower for removal of trace metal ions in chemicals by adsorption distillation to obtain electronic grade chemicals above G3 grade.

[0023] Furthermore, the chemicals include general wet electronic chemicals such as N-methylpyrrolidone (NMP), isopropyl alcohol (IPA), and propylene glycol monomethyl ether acetate (PMA).

[0024] Furthermore, the number of theoretical plates of the distillation tower is 30-50, and the reflux ratio is 2-20.

[0025] Furthermore, the distillation tower is subjected to multiple acid washings and repeated alkaline passivation.

[0026] Furthermore, a single or multiple distillation towers can be used in series.

[0027] Furthermore, the metal ion content in the obtained electronic-grade chemicals is less than 1 ppb.

[0028] The beneficial effects of the present invention are: The present invention prepares 3D printing hydrogel ink by using a photoinitiator, a light absorber, a solvent and a cross-linking agent that do not contain metal ions, and prints it into an adsorption distillation filler using a 3D printing photocuring technology. The prepared adsorption distillation filler is then loaded into a distillation tower, thereby removing trace metal ions in chemicals through the coupling of adsorption and distillation processes. The present invention can effectively reduce the plates of the distillation tower, avoid the cost of building an additional adsorption tower, and can remove metal ions in NMP, IPA, and PMA to less than 1 ppb, thereby achieving the preparation of electronic-grade chemicals above G3 level, and providing a reference for the separation and purification of industrial-grade chemicals to prepare electronic-grade chemicals. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the device for preparing G3 grade NMP in Example 1.

[0030] Figure 2 This is the SEM image of the adsorption distillation filler prepared in Example 1.

[0031] Figure 3 The infrared spectra of lysine (ML), sodium lignin sulfonate (MS), the prepared adsorption distillation filler (SLH-2) and the filler after adsorbing Cu metal ions in NMP (SLH-2-Cu) are shown in Example 1.

[0032] Figure 4 X-ray diffraction patterns of the adsorption distillation filler (SLH-2) prepared in Example 1 and its adsorption of Cu metal ions in NMP (SLH-2-Cu).

[0033] Figure 5 This is a comparison diagram of the adsorption distillation filler prepared in Example 1 and its actual product after adsorbing Cu metal ions in NMP.

[0034] Figure 6 Schematic diagram of the device for preparing G3 grade IPA in Example 2.

[0035] Figure 7 Schematic diagram of the device for preparing G3 grade PMA in Example 3. DETAILED DESCRIPTION

[0036] An adsorption and distillation filler based on hydrogel 3D printing, the preparation of which includes the following steps: (1) Weigh appropriate amounts of L-lysine, reactive monomer, ammonium persulfate, crosslinking agent, photoinitiator and light absorber in a mass ratio of 1:(1-3):5:1:(0.4-1):(0.1-0.5) and add them into a beaker, and add electronic grade ammonia water, acrylic acid and ultrapure water without metal ions while stirring to prepare a hydrogel ink for 3D printing; the amounts of electronic grade ammonia water, acrylic acid and ultrapure water account for 21-30%, 38-49% and 20-30% of the mass of the hydrogel ink for 3D printing, respectively; (2) Designing a three-dimensional model of a filler with a foam structure, a corrugated structure, a columnar structure, etc. using computer-aided modeling software, and then processing the data of the modeled three-dimensional model using slicing software, and then placing the 3D printing hydrogel ink prepared in step (1) in a printer material box for photocuring 3D printing to obtain a photocured hydrogel adsorption distillation filler structure; the light source wavelength used in the photocuring 3D printing is 320-500nm, the light source intensity is 300-500mW, the exposure time of each layer is 10-30s, and the slice thickness is 0.1-0.2mm; (3) The hydrogel adsorption distillation filler structure prepared in step (2) is ion exchanged with a hydrochloric acid solution having a concentration of 1-5 M for 2-12 hours, and freeze-dried at -40-50° C. to obtain the adsorption distillation filler, which is placed in a drying oven for later use.

[0037] Wherein, the reaction monomer in step (1) is cellulose or sodium lignin sulfonate. The cross-linking agent is N,N-methylenebisacrylamide or polyethylene glycol diacrylate. The photoinitiator is (2,4,6-trimethylbenzoyl) diphenylphosphine oxide (TPO) or ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L). The light absorber is tartrazine, riboflavin or ultraviolet absorber UV-P.

[0038] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0039] The reagents used to prepare the hydrogel in the experiment were analytically pure and commercially available. The conductivity of the ultrapure water used was 18.2 MΩ and the TOC value was less than 5 ppb.

[0040] The concentration of metal ions in the experiment was tested using ICP (ICPE-9000) and ICP-MS (ICAP RQ, ThermoFisher Scientific, Germany). The purity of the solvent after adsorption was tested using gas chromatography (Agilent 8890 GCSystem). The actual adsorption experiment was carried out in a Class 1000 clean laboratory, and all the instruments used in the experiment were made of PFA.

[0041] Example 1 Weigh 0.03 g lysine, 0.06 g sodium lignin sulfonate, 0.15 g ammonium persulfate, 0.03 g N,N-methylenebisacrylamide, 0.018 g TPO, and 0.005 g lemon yellow in a 250 mL beaker, then slowly add 7.5 g acrylic acid, 5 g ultrapure water, and 4.5 g electronic grade ammonia water, and stir for 1 h to obtain a hydrogel ink for 3D printing. Then put the obtained hydrogel ink into a smooth 3D printing material box, and use a light-curing 3D printer to print according to the model program (the light source wavelength of the 3D printer is 350 nm, the intensity is 380 mW, the slice thickness is 0.1 nm, and the exposure time of each layer is 20 s) to obtain a light-cured hydrogel adsorption distillation filler. The obtained hydrogel adsorption distillation filler is then ion-exchanged with a 1M hydrochloric acid solution for 2 h, and then freeze-dried at -45 ° C to obtain an adsorption distillation filler.

[0042] The prepared adsorption distillation filler is loaded into a distillation tower, and a single distillation tower is used to prepare G3 grade NMP. The schematic diagram of the device is shown in Figure 1 The number of theoretical plates of the distillation tower 1 used is 40, and the reflux ratio is 8. The product indicators are shown in Table 1.

[0043] Table 1 Adsorption effect of prepared adsorption distillation fillers on different metal ions in NMP

[0044] Figure 2 This is the SEM image of the prepared adsorption distillation filler. From the image, it can be seen that its surface contains rich porous structures, which can make the material surface show more active sites, which may also be the key to its better adsorption performance.

[0045] Figure 3 The infrared spectra of the used lysine (ML), sodium lignin sulfonate (MS), the prepared adsorption distillation filler (SLH-2), and the filler after adsorbing Cu metal ions in NMP (SLH-2-Cu). As can be seen in the figure, in the infrared spectrum of lysine, ~3440 cm -1 The peak at 1580 cm is the stretching vibration peak of -OH or -COOH; -1 The serrated absorption peak of lysine is at 1570 cm -1 The peak at 1120 cm is the vibration peak of the C=C skeleton in the benzene ring. -1 The -O- stretching vibration peaks are at 1040, 657 and 532 cm -1 The peak at 1564 cm is the stretching vibration peak of the sulfonate group. -1 and 549cm -1The peak at is attributed to -NH 2 -and-SO 3 In the H functional diagram, the filler has the absorption peaks of both monomers, indicating that the filler was successfully prepared. After the filler adsorbed Cu metal ions, the position and intensity of some absorption peaks (marked with gray substrate) changed, indicating that the metal ions and the functional groups on the surface of the hydrogel were complexed.

[0046] Figure 4 The X-ray diffraction diagram of the prepared adsorption distillation filler (SLH-2) and after it adsorbed Cu metal ions in NMP (SLH-2-Cu). As can be seen from the figure, the filler sample itself has no XRD diffraction peak, but after adsorbing Cu metal ions, there is an obvious XRD diffraction peak, which corresponds to a cuprammonium complex, indicating that the filler successfully adsorbed copper ions.

[0047] Figure 5 The prepared adsorption distillation and the physical comparison diagram after adsorbing Cu metal ions in NMP are shown in the figure. It can be seen from the figure that the filler is yellow before adsorption and turns blue after adsorption, which indicates that a layer of copper ions is covered on the surface of the filler.

[0048] Example 2 0.03 g lysine, 0.03 g cellulose, 0.15 g ammonium persulfate, 0.03 g N,N-methylenebisacrylamide, 0.012 g TPO, and 0.005 g lemon yellow were weighed and added into a 250 mL beaker, followed by slow addition of 15.7 g acrylic acid, 10 g ultrapure water, and 8.9 g electronic grade ammonia water, and stirred for 1 h to obtain a hydrogel ink for 3D printing. The obtained hydrogel ink was then placed into a smooth 3D printing material box, and printed using a light-curing 3D printer according to the model program (the light source wavelength of the 3D printer was 350 nm, the intensity was 380 mW, the slice thickness was 0.1 nm, and the exposure time for each layer was 20 s) to obtain a light-cured hydrogel adsorption distillation filler. The obtained hydrogel adsorption distillation filler was then ion-exchanged with a 1 M hydrochloric acid solution for 2 h, and then freeze-dried at -45 ° C to obtain an adsorption distillation filler.

[0049] The prepared adsorption distillation filler is loaded into a distillation tower, and two distillation towers are connected in series to prepare G3 grade IPA. The schematic diagram of the device is shown in FIG. Figure 6 The theoretical plate number of the distillation tower 2 is 40, and the reflux ratio is 10; the theoretical plate number of the distillation tower 3 is 45, and the reflux ratio is 10. The product indicators are shown in Table 2.

[0050] Table 2 Adsorption effect of prepared adsorption distillation fillers on different metal ions in IPA

[0051] Example 3 0.03 g lysine, 0.09 g cellulose, 0.15 g ammonium persulfate, 0.03 g N,N-methylenebisacrylamide, 0.024 g TPO, and 0.005 g lemon yellow were weighed and added into a 250 mL beaker, followed by slow addition of 15.7 g acrylic acid, 10 g ultrapure water, and 8.9 g electronic grade ammonia water, and stirred for 1 h to obtain hydrogel ink for 3D printing. The obtained hydrogel ink was then placed into a smooth 3D printing material box, and printed using a light-curing 3D printer according to the model program (the light source wavelength of the 3D printer was 350 nm, the intensity was 380 mW, the slice thickness was 0.1 nm, and the exposure time for each layer was 20 s) to obtain a light-cured hydrogel adsorption distillation filler. The obtained hydrogel adsorption distillation filler was then ion-exchanged with a 1 M hydrochloric acid solution for 2 h, and then freeze-dried at -45 ° C to obtain an adsorption distillation filler.

[0052] The prepared adsorption distillation filler was loaded into a distillation tower, and three distillation towers were connected in series to prepare G3 grade PMA. The schematic diagram of the device is shown in Figure 7 The theoretical plate number of the distillation tower 4 is 20, and the reflux ratio is 5; the theoretical plate number of the distillation tower 5 is 25, and the reflux ratio is 10; the theoretical plate number of the distillation tower 6 is 20, and the reflux ratio is 8. The product indicators are shown in Table 3.

[0053] Table 3 Adsorption effect of prepared adsorption distillation fillers on different metal ions in PMA

[0054] It can be seen from the above that after adsorption distillation, the metal ions in IPA, NMP and PMA in Examples 1-3 can be well removed, and their concentrations are all below 1 ppb, meeting the requirements of G3 electronic grade chemicals.

[0055] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. An adsorption and distillation filler based on hydrogel 3D printing, characterized in that: The preparation method comprises the following steps: (1) L-lysine, a reactive monomer, ammonium persulfate, a crosslinking agent, a photoinitiator, and a light absorber are mixed, and electronic grade ammonia, acrylic acid, and ultrapure water are added under stirring to prepare a 3D printing hydrogel ink; (2) According to the designed filler three-dimensional model, photocuring 3D printing is performed using the 3D printing hydrogel ink prepared in step (1) to obtain a photocured hydrogel adsorption distillation filler structure; (3) The hydrogel adsorption distillation filler structure obtained in step (2) is subjected to ion exchange with a hydrochloric acid solution, and freeze-dried to obtain the adsorption distillation filler.

2. The adsorption distillation packing according to claim 1, characterized in that: In step (1), the reaction monomer is cellulose or sodium lignin sulfonate; the cross-linking agent is N,N-methylenebisacrylamide or polyethylene glycol diacrylate; the photoinitiator is (2,4,6-trimethylbenzoyl) diphenylphosphine oxide or ethyl 2,4,6-trimethylbenzoylphenylphosphonate; and the light absorber is tartrazine, riboflavin or ultraviolet absorber UV-P.

3. The adsorption distillation packing according to claim 1, characterized in that: The mass ratio of L-lysine, reactive monomer, ammonium persulfate, crosslinking agent, photoinitiator and light absorber used in step (1) is 1:(1-3):5:1:(0.4-1):(0.1-0.5).

4. The adsorption distillation packing according to claim 1, characterized in that: In step (1), the amounts of electronic grade ammonia water, acrylic acid and ultrapure water used account for 21-30%, 38-49% and 20-30% of the mass of the obtained 3D printing hydrogel ink, respectively.

5. The adsorption distillation packing according to claim 1, characterized in that: The light source wavelength used in the light-curing 3D printing in step (2) is 320-500 nm, the light source intensity is 300-500 mW, the exposure time of each layer is 10-30 s, and the slice thickness is 0.1-0.2 mm.

6. The adsorption distillation packing according to claim 1, characterized in that: The concentration of the hydrochloric acid solution used in step (3) is 1-5 M; the ion exchange time is 2-12 hours; and the freeze-drying temperature is -40~50°C.

7. Use of the adsorption distillation filler according to claim 1 in removing trace metal ions in chemicals by adsorption distillation, characterized in that: The adsorption distillation filler is loaded into a distillation tower for removing trace metal ions in chemicals by adsorption distillation to obtain electronic grade chemicals above G3 grade.

8. The use according to claim 7, characterized in that: The chemicals include N-methylpyrrolidone, isopropyl alcohol, and propylene glycol monomethyl ether acetate.

9. The use according to claim 7, characterized in that: The number of theoretical plates of the distillation tower is 30-50, and the reflux ratio is 2-20.

10. The use according to claim 7, characterized in that: The metal ion content in the obtained electronic-grade chemicals is below 1 ppb.

Citation Information

Patent Citations

  • Metal ion imprinted hydrogel adsorbing material with interpenetrating polymer network (IPN) structure and preparation method for metal ion imprinted hydrogel adsorbing material

    CN102824899A

  • Method for preparing biomass-based conductive hydrogel by 3D printing

    CN110358115A

  • Preparation method of photo-cured 3D printing bio-compatible silk fibroin hydrogel

    CN114075339A

  • Trace metal ion adsorbent in NMP system

    CN116440877A

  • Hydrogels for vocal cord and soft tissue augmentation and repair

    US20100055184A1